The Effectiveness of Cognitive-Behavioral Therapy in Decreasing Depression and Increasing Happiness and Life Satisfaction - Alireza Nazari Anamagh, Niloofar Mikaeil, Seyed Teymur Seyedi Asl, Mohammad Narimani, (Opción, 2019)
This study examined the effectiveness of cognitive-behavioral therapy (CBT) in improving depression, happiness, and satisfaction with life in male high school students. The current quasi-experimental study had a pretest-posttest design with a control group. The mean depression score significantly (P < 0.001) decreased in the intervention group compared with the control group in post-test. Also, the CBT group showed significant increases in happiness (P < 0.001) and satisfaction with life (P < 0.001) compared with the control group. In conclusion, CBT proves effective in improving depression, happiness, and satisfaction with life in high school students.